The Effect of the New Lupeol Derivatives on Human Skin Cells as Potential Agents in the Treatment of Wound Healing - Magdalena Anna Malinowska; Elżbieta Sikora; Joanna Stalińska; Jan Ogonowski; Justyna Drukała (Biomolecules, 2021)
Skin barrier damage can be the result of various external factors including heat, radiation, chemicals and many others. Any interruption of the skin barrier integrity causes the exposure of the organism to harmful environmental factors. Therefore, there is an urgent need to develop novel therapeutics characterized by high bioavailability and effectiveness in skin damage recovery. Birch bark is known as a clinically proven, traditional medicinal remedy to accelerate wound healing. Lupeol, one of the main birch bark ingredients, shows a wide range of biological activity beneficial to the skin. The purpose of the research was to determine the influence of new lupeol derivatives on keratinocyte and fibroblast migration and proliferation, as well as to investigate various mechanisms of their antioxidant activity. The chemical modification of lupeol structure was intended to obtain more effective therapeutics characterized by higher bioavailability, permeability and safety of use. The novel triterpenes presented in this study were evaluated as the potential active ingredients preventing skin tissue degradation. Lupeol esters influence skin cells’ motility and proliferation. Importantly, they are able to reduce reactive oxygen species and act indirectly by protecting the skin protein structure from being oxidized by free radicals.